2005
DOI: 10.1002/srin.200506044
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Ring Rolling Technology - Part 2: Investigation of Process Behaviour and Production Equipment

Abstract: steel research int. 76 (2005) NO.7 steel research int. 76 (2005) NO.7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…Δb 1 and Δb 2 are the maximum feed amounts per revolution determined by Eqs. (11) and (18), respectively, by setting the friction coefficient as 0.35. Δb s is the numerical simulation result obtained by using finite element software ABAQUS.…”
Section: Gripping Condition Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Δb 1 and Δb 2 are the maximum feed amounts per revolution determined by Eqs. (11) and (18), respectively, by setting the friction coefficient as 0.35. Δb s is the numerical simulation result obtained by using finite element software ABAQUS.…”
Section: Gripping Condition Modificationmentioning
confidence: 99%
“…Many researchers [7][8][9][10][11] including Johnson, Mamalis, and Hawkyard studied the rolling force and torque by using experimental and theoretical methods. Among them, Johnson et al found a linear relationship between rolling force and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of resources have successively devoted to the development of ring rolling technique in many countries like America, Russia, Germany, Japan and China, etc. Allwood et al (2005aAllwood et al ( , 2005b) made a thorough review of ring rolling work published in English and German languages by 2004, including technological characteristics of ring rolling, application of ring rolled products, comparison of ring rolling with other alternative process, previous reviews of ring rolling, key challenges for ring rolling, the evolution of ring rolling technology and equipment, etc. Since the 21st century, the situation, such as globalisation of manufacturing industry, rapid development of Chinese economic, scarcity of traditional energy resources and competition of cutting-edge technique, has proposed an intense demand of high-performance ring components.…”
Section: Introductionmentioning
confidence: 99%
“…For a kind of ring with small hole and deep groove, Hua et al [8] built analytical models of rolling power, torque and force by means of the classic plastic mechanics theory of upper bound method combined with static analysis and calculation of kinematical admissible velocity field. Allwood et al [9,10] summarized ring rolling technology and previous researches, including the evolution of rolling equipment design, the methods used to research ring rolling, developments in productive process, and characteristics of all kinds of rings.…”
Section: Introductionmentioning
confidence: 99%